2000
DOI: 10.1007/s101890050003
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a Gaussian random copolymer chain at an interface

Abstract: We consider the adsorption of an isolated, Gaussian, random, and quenched copolymer chain at an interface. We first propose a simple analytical method to obtain the adsorption/depletion transition, by averaging over the disorder the partition function instead of the free energy. The adsorption thresholds obtained by previous authors at a solid/liquid and at a liquid/liquid interface for multicopolymer chains can be rederived using this method. We also compare the adsorption thresholds obtained for bimodal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…As is well-known from experiment, in the presence of selective interfaces for which the energy gain for a monomer in the favored solvent is large, the hydrophobic and polar blocks of a copolymer chain try to stay on different sides of the boundary between the two solvents, leading thus to a major reduction of the interfacial tension which has important technological applications, i.e., for compatilizers, thickeners, or emulsifiers. Not surprisingly, during the past two decades the problem has gained a lot of attention also from theory as well as from computer experiment. While in earlier studies attention has been mostly focused on diblock copolymers 6,8 due to their relatively simple structure, the scientific interest shifted later to random HP copolymers at penetrable interfaces. , In contrast, our investigations have focused mainly on the impact of block size M on the static properties and localization kinetics of regular multiblock copolymers at the phase boundary between the two immiscible solvents. We showed that these are well described by a simple scaling theory 1,3 in terms of the total copolymer length N (the number of repeating units in the chain), the block size M (the number of consecutive monomers of the same kind), and the selectivity parameter χ, that is, the energy gained by a monomer when moving into the more favorable solvent.…”
Section: Introductionmentioning
confidence: 99%
“…As is well-known from experiment, in the presence of selective interfaces for which the energy gain for a monomer in the favored solvent is large, the hydrophobic and polar blocks of a copolymer chain try to stay on different sides of the boundary between the two solvents, leading thus to a major reduction of the interfacial tension which has important technological applications, i.e., for compatilizers, thickeners, or emulsifiers. Not surprisingly, during the past two decades the problem has gained a lot of attention also from theory as well as from computer experiment. While in earlier studies attention has been mostly focused on diblock copolymers 6,8 due to their relatively simple structure, the scientific interest shifted later to random HP copolymers at penetrable interfaces. , In contrast, our investigations have focused mainly on the impact of block size M on the static properties and localization kinetics of regular multiblock copolymers at the phase boundary between the two immiscible solvents. We showed that these are well described by a simple scaling theory 1,3 in terms of the total copolymer length N (the number of repeating units in the chain), the block size M (the number of consecutive monomers of the same kind), and the selectivity parameter χ, that is, the energy gained by a monomer when moving into the more favorable solvent.…”
Section: Introductionmentioning
confidence: 99%
“…For strongly selective interfaces, when the energy gain for a monomer in the favored solvent is large, the hydrophobic and polar blocks of a copolymer chain try to stay on different sides of the interface leading thus to a major reduction of the interfacial tension between the immiscible liquids or melts which has important technological applications, e.g., for compatilizers, thickeners or emulsifiers. Not surprisingly, during the last two decades the problem has gained a lot of attention from experiment and theory as well as from computer experiment. While in earlier studies attention has been mostly focused on diblock copolymers 2,4 due to their relatively simple structure, the scientific interest shifted later to random HP-copolymers at penetrable interfaces. , Until recently though, the properties of regular multiblock copolymers, especially with emphasis on their dependence on block length M , have remained largely unexplored. This has been a driving force for our research, since experimentalists are now able to synthesize polymers with an increased variety of controlled structures.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, during the last two decades the problem has gained a lot of attention from experiment [1][2][3][4], theory [5][6][7][8][9] as well as from computer experiment [10][11][12][13][14]. While in earlier studies attention has been mostly focused on diblock copolymers [2,4] due to their relatively simple structure, the scientific interest shifted later to random HP copolymers at penetrable interfaces [6][7][8][9]14]. Until recently though, the properties of regular multiblock copolymers (i.e.…”
mentioning
confidence: 99%